Adolescence as a period of vulnerability and intervention in schizophrenia: Insights from the MAM model. (November 2016) - Gomes, Felipe V.; Rincón-Cortés, Millie; Grace, Anthony A.
Highlights: Adolescence is a critical period for risk factors that predispose to schizophrenia. The DA system and the PFC undergo dramatic changes during this period. We review effects of stress and drug exposure in the MAM model of schizophrenia. Adolescence is a sensitive period for exacerbation and prevention of schizophrenia. Abstract: Adolescence is a time of extensive neuroanatomical, functional and chemical reorganization of the brain, which parallels substantial maturational changes in behavior and cognition. Environmental factors that impinge on the timing of these developmental factors, including stress and drug exposure, increase the risk for psychiatric disorders. Indeed, antecedents to affective and psychotic disorders, which have clinical and pathophysiological overlap, are commonly associated with risk factors during adolescence that predispose to these disorders. In the context of schizophrenia, psychosis typically begins in late adolescence/early adulthood, which has been replicated by animal models. Rats exposed during gestational day (GD) 17 to the mitotoxin methylazoxymethanol acetate (MAM) exhibit behavioral, pharmacological, and anatomical characteristics consistent with an animal model of schizophrenia. Here we provide an overview of adolescent changes within the dopamine system and the PFC and review recent findings regarding the effects of stress and cannabis exposure during the peripubertal period as risk factors for the emergence of schizophrenia-like deficits. Finally, we discuss peripubertal interventions appearing to circumvent the emergence of adult schizophrenia-like deficits.